Pengaruh Kecerdasan Emosional, Komitmen Organisasional dan Organizational Citizenship Behavior terhadap Kinerja - Permata Sakti; Rossanto Dwi Handoyo; Ake Wihadanto (UNIVERSITAS MUHAMMADIYAH SUMATERA UTARA, 2020)
Badan Pusat Statistik has a vision as a provider of quality data needed in the planning, monitoring, and evaluating development for the government and the community. The current focus of BPS is on improving data quality and excellent service so that the role of BPS staff, especially the District Statistics Coordinator (KSK) in improving data quality, is very important. This study aims to analyze the effect of emotional intelligence, organizational commitment, and Organizational Citizenship Behavior on the performance of KSK in Statistics of Regency / Municipality in East Java as many as 447 people using SmartPLS software. The results showed that organizational commitment had a positive effect but did not have a significant impact on the performance of KSK. In contrast, OCB and emotional intelligence partially had a positive and significant effect on KSK performance. Other factors influence variable emotional intelligence, organizational commitment, and OCB influence the performance of KSK by 75.89 percent and by 24.11 percent.